Simon Cowley at 180 m of His 200 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S.
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Simon Cowley at 180 m of His 200 m Race at the 1999 Pan Pacific Championships in Sydney. Simon Cowley's stroke is efficient and effective. It is characterized by a controlled smoothness and continuity, something that is rarely seen in other top breaststroke actions. The value of not having any obvious "forced" or exaggerated thrusts and contractions, or emphasized extensions for streamlining in the overall movement pattern, should be determined. For this swimmer, this approach obviously works.